Constant Light Dysregulates Cochlear Circadian Clock and Exacerbates Noise-Induced Hearing Loss - Yang, Chao-Hui (Int J Mol Sci, 2020)
Noise-induced hearing loss is one of the major causes of acquired sensorineural hearing loss in modern society. While people with excessive exposure to noise are frequently the population with a lifestyle of irregular circadian rhythms, the effects of circadian dysregulation on the auditory system are still little known. Here, we disturbed the circadian clock in the cochlea of male CBA/CaJ mice by constant light (LL) or constant dark. LL significantly repressed circadian rhythmicity of circadian clock genes Per1, Per2, Rev-erbα, Bmal1, and Clock in the cochlea, whereas the auditory brainstem response thresholds were unaffected. After exposure to low-intensity (92 dB) noise, mice under LL condition initially showed similar temporary threshold shifts to mice under normal light–dark cycle, and mice under both conditions returned to normal thresholds after 3 weeks. However, LL augmented high-intensity (106 dB) noise-induced permanent threshold shifts, particularly at 32 kHz. The loss of outer hair cells (OHCs) and the reduction of synaptic ribbons were also higher in mice under LL after noise exposure. Additionally, LL enhanced high-intensity noise-induced 4-hydroxynonenal in the OHCs. Our findings convey new insight into the deleterious effect of an irregular biological clock on the auditory system.